Formation of prismatic loops from C15 Laves phase interstitial clusters in body-centered cubic iron. (15th March 2015) - Zhang, Yongfeng; Bai, Xian-Ming; Tonks, Michael R.; Biner, S. Bulent
Abstract : This work reports the transformation of C15 Laves phase interstitial clusters to prismatic loops in body-centered cubic iron. Molecular dynamics simulations and elasticity analysis show that, within a certain size range, C15 clusters are more stable than loops, but the relative stabilities are reversed beyond this range. C15 clusters can consistently grow by absorbing interstitials at small sizes and transforming into loops later. Both 〈 1 0 0 〉 and 〈 1 1 1 〉 / 2 loops may result from the transformation, revealing a new formation mechanism for 〈 1 0 0 〉 loops.